2022
DOI: 10.3389/fnins.2022.825063
|View full text |Cite
|
Sign up to set email alerts
|

Excitation and Inhibition Imbalance in Rett Syndrome

Abstract: A loss of the excitation/inhibition (E/I) balance in the neural circuit has emerged as a common neuropathological feature in many neurodevelopmental disorders. Rett syndrome (RTT), a prevalent neurodevelopmental disorder that affects 1:10,000–15,000 women globally, is caused by loss-of-function mutations in the Methyl-CpG-binding Protein-2 (Mecp2) gene. E/I imbalance is recognized as the leading cellular and synaptic hallmark that is fundamental to diverse RTT neurological symptoms, including stereotypic hand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 195 publications
1
15
0
Order By: Relevance
“…Through this study, three synaptic pathways enriched in the skyblue module were identified, namely the cholinergic, glutamatergic, and GABAergic pathways. A loss of excitation/inhibition (E/I) balance in the neural circuit is a major hallmark of RTT pathology, causing many neurological symptoms, such as loss of purposeful hand movements, impaired motor coordination, breathing irregularities, and seizures, amongst others [ 10 ]. This loss of E/I balance is caused by MeCP2 deficiency, leading to a dysregulation of the glutamatergic and GABAergic pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through this study, three synaptic pathways enriched in the skyblue module were identified, namely the cholinergic, glutamatergic, and GABAergic pathways. A loss of excitation/inhibition (E/I) balance in the neural circuit is a major hallmark of RTT pathology, causing many neurological symptoms, such as loss of purposeful hand movements, impaired motor coordination, breathing irregularities, and seizures, amongst others [ 10 ]. This loss of E/I balance is caused by MeCP2 deficiency, leading to a dysregulation of the glutamatergic and GABAergic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…MeCP2 also acts as a transcription activator to regulate gene expression by either long-range chromatin remodeling or by regulating RNA splicing [ 7 , 8 , 9 ]. MeCP2-deficiency leads to an excitation/inhibition (E/I) imbalance in the brain and is recognized as the leading cellular and synaptic hallmark of the disorder resulting in stereotypic hand movements, impaired motor coordination, breathing irregularities, seizures, and learning/memory dysfunctions [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…34,35 Imbalance of excitatory/ inhibitory circuits may be one of the important causes of RTT. 36 In GABAergic neurons derived from the RTT-iPSCs, GABAergic circuit disruption and decrease of acetylated α-tubulin were also found.…”
Section: Cdkl5mentioning
confidence: 94%
“…This result may be caused by the downregulated expression of neuron‐specific membrane transporter K + /Cl + cotransporter (KCC2) mediated by RE1‐silencing transcription factor (REST), a neuronal gene inhibitor in RTT, which is essential for maintaining excitatory balance in the brain 34,35 . Imbalance of excitatory/inhibitory circuits may be one of the important causes of RTT 36 . In GABAergic neurons derived from the RTT‐iPSCs, GABAergic circuit disruption and decrease of acetylated α‐tubulin were also found 37 …”
Section: Research Progress On the Pathogenesis Of Rtt Using Cell Modelsmentioning
confidence: 99%
“…Through this study, three synaptic pathways enriched in the skyblue module were identified, namely the cholinergic, glutamatergic, and GABAergic pathways. A loss of excitation/inhibition (E/I) balance in the neural circuit is a major hallmark of RTT pathology, causing many neurological symptoms such as loss of purposeful hand movements, impaired motor coordination, breathing irregularities and seizures amongst others [55]. This loss of E/I balance is caused by MeCP2 deficiency leading to dysregulation of the glutamatergic and GABAergic pathways, furthermore downstream genes affected in RTT such as BDNF play an important role influencing neurotransmission activity.…”
Section: Meta-analysis Shows Commonly Dysregulated Synaptic Pathwaysmentioning
confidence: 99%